2011
DOI: 10.1016/j.tripleo.2011.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscope and x-ray diffraction analysis assisting the diagnosis of a sialolith in the parotid duct

Abstract: A 60-year-old man presented with a painless blackish well defined nodule in the parotid duct region of the left buccal mucosa. The nodule was ϳ1.0 cm in diameter, freely movable, and present 2 months (Fig. 1). The medical history was noncontributory, and the main clinical diagnosis was of a foreign body. An excisional biopsy was performed under local anesthesia, and 3 blackened stone-like fragments associated with soft tissue were removed from the parotid duct and submitted to histopathologic examination.Macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The longer length and tortuous nature of the submandibular duct with the thicker consistency of submandibular saliva likely contribute to this predilection. Although rarer in occurrence, sialoliths can also develop in ducts of minor salivary glands, the sublingual gland, and, as in this case, the parotid gland . The rarity of sialoliths in the parotid gland duct is likely due to the serous nature of parotid gland saliva.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The longer length and tortuous nature of the submandibular duct with the thicker consistency of submandibular saliva likely contribute to this predilection. Although rarer in occurrence, sialoliths can also develop in ducts of minor salivary glands, the sublingual gland, and, as in this case, the parotid gland . The rarity of sialoliths in the parotid gland duct is likely due to the serous nature of parotid gland saliva.…”
Section: Discussionmentioning
confidence: 70%
“…Although rarer in occurrence, sialoliths can also develop in ducts of minor salivary glands, the sublingual gland, and, as in this case, the parotid gland. 1,2 The rarity of sialoliths in the parotid gland duct is likely due to the serous nature of parotid gland saliva. Formation of a sialolith involves the concentric deposition of calcified material around a central nidus.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of stones in the salivary extraglandular system has been predominantly attributed to slow salivary flow, salivary stagnation, and intricate metabolic events (Waseem and Forte, 2005). Various studies (Kinoshita et al , 2008; Su et al , 2010; Ribeiro et al , 2011) have demonstrated the microstructure of sialoliths and features of electrolyte alteration in saliva during pathologic states; however, less attention has been paid to the macroscopic effects of changes in salivary flow. Using CFD, we explored the changes in the salivary flow field of Stensen’s duct, which we believe may affect the symptoms and prognosis of this pathologic condition.…”
Section: Discussionmentioning
confidence: 99%